Efectiveness of Mindfulness in Alleviating Hypertension and Anxiety in Adults Patients - Irawan. AM, Ady; Anwar, Syamsul; Anggraini, Dewi; Khasanah, Uswatul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Anxiety often accompanies the clinical symptoms of hypertension in patients. Mindfulness stands as a non-pharmacological nursing approach aimed at lowering both blood pressure and anxiety levels. This study aimed to evaluate how effective mindfulness is in lowering blood pressure and reducing anxiety among hypertensive patients. The study employed a case study design with the sample size determined through G*Power analysis. Eight participants were purposively selected for the study. All participants were allocated to a single treatment group. Mindfulness sessions were conducted over eight sessions, with blood pressure measurements taken using a digital sphygmomanometer and anxiety levels assessed using the Zung Self-Rating Anxiety Scale (Zung-SARS) both before and after the intervention. The study found a significant mean difference in systolic blood pressure (8.25, SD=0.590) mmHg, diastolic blood pressure (4.38, SD=0.962) mmHg, and anxiety levels (48.5, SD=3.63) before and after the intervention. Mindfulness demonstrated statistical significance in reducing both systolic (14(7), p0.001, effect size=4.94) and diastolic (4.55(7), p0.05, effect size=1.61) blood pressure, as well as anxiety levels (25.5(7), p0.001, effect size=8.92). Mindfulness has a positive impact on reducing blood pressure and anxiety in the adult group of patients with hypertension. The application of mindfulness in hypertension management contributes to improving the quality of life of patients. Collaborative efforts between medical personnel and patients need to be encouraged to achieve the best results in hypertension management.Keywords: mindfulness, hypertension, anxiety, adult patient.